2014
DOI: 10.1136/bjophthalmol-2014-305132
|View full text |Cite
|
Sign up to set email alerts
|

Lateral incomitancy and surgical results in intermittent exotropia

Abstract: Surgical outcomes in ULR and BLR for intermittent exotropia correction showed no association with preLI+. The prevalences of significant LI were unchanged after surgery in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The factors reported to affect the surgical outcome after exotropia surgery vary widely, including age at surgery, preoperative angle of deviation, refractive errors, type of surgery, lateral incomitance and early postoperative ocular alignment. [6, 19, 2629] In this study, younger age at onset of exotropia and smaller amount of postoperative overcorrection were associated with recurrence, and presence of neurodevelopmental disabilities and greater amount of postoperative overcorrection were risk factors for final overcorrection in the multivariable analyses. Kim et al reported that younger age at diagnosis and surgery and early postoperative overcorrection of ≥ 20 PD were predisposing factors for consecutive esotropia.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The factors reported to affect the surgical outcome after exotropia surgery vary widely, including age at surgery, preoperative angle of deviation, refractive errors, type of surgery, lateral incomitance and early postoperative ocular alignment. [6, 19, 2629] In this study, younger age at onset of exotropia and smaller amount of postoperative overcorrection were associated with recurrence, and presence of neurodevelopmental disabilities and greater amount of postoperative overcorrection were risk factors for final overcorrection in the multivariable analyses. Kim et al reported that younger age at diagnosis and surgery and early postoperative overcorrection of ≥ 20 PD were predisposing factors for consecutive esotropia.…”
Section: Discussionmentioning
confidence: 60%
“…All patients underwent complete ophthalmological examinations before surgery, and the following data were recorded: gestational age, birth weight, sex, age at onset of deviation, age at diagnosis of exotropia, age at surgery, cycloplegic refraction, distance and near deviation angle, constancy of deviation, associated strabismus (dissociated vertical deviation, oblique muscle dysfunction, vertical deviation), presence of eye dominance, lateral incomitance (decrease in distant deviation of > 5 PD in a lateral gaze) [19], stereoacuity, and fusional status. Deviation was measured using the alternate prism and cover test at a distance (6 m) and close-up (33 cm) for the primary gaze, with appropriate spectacle correction when required.…”
Section: Methodsmentioning
confidence: 99%
“… 41 , 43 In a recent study, 63/155 patients (41%) undergoing surgery for intermittent exotropia had lateral incomitance of >5 prism-diopters. 44 For patients with sizeable incomitance in primary gaze, such as those identified in our study, one might consider performing slightly asymmetrical surgery to obtain optimal results. For example, in a patient with a right larger than left exotropia, one might recess the right more than the left lateral rectus.…”
Section: Discussionmentioning
confidence: 96%
“…Yoon and Kim reported significant postoperative lateral incomitance in the patients who had unilateral lateral rectus recession in comparison to the patients who had symmetrical bilateral lateral rectus recession (P = 0.006). 25 …”
Section: Discussionmentioning
confidence: 99%